Folklore formulae of Ukrainian wedding songs’ texts - Svishch , Natalia (Current issues of Ukrainian linguistics: theory and practice, 2018)
The present article researches the functioning of the formulaic diction in the Ukrainian wedding songs’ texts. It investigates the underlying mythological and ritual basis that caused the emergence of the textual component as it preserved in contemporary Ukrainian folklore. Textual sources analyzed in the article are the most relevant for the purposes of the current investigation as they were transcribed immediately from the alive performance as early as in the XIX century by prominent pioneers of scientific folkloristic and ethnography Zorian Dolenga-Chodakowky, Stepan Rudansky and others. The notion of formulae accepted in the present study regards the formula as any word or words’ combination that has stable mythological and ritual meaning and is common in the poetical diction of certain nation. Thus a series of poetical formulae were discovered in the texts of the Ukrianian traditional wedding songs. They concern mainly the following thematic groups: people, human body parts, birds of the upper world, animals of the middle world, animal of the nether world, natural objects, and artificial objects (many of the latter execute special symbolic functions in the wedding rite itself).
Keywords: Ukrainian language, Ukrainian folklore, formula, wedding, song, rite